Базові елементи й особливості підготовки журналіста-оператора - Максимович, Мирослав; Maksymovich, Myroslav (Видавництво Львівської політехніки, 2018)
Розглянуто базові елементи й особливості підготовки журналіста-оператора, які ґрунтуються на комплексному підході до викладу фахових дисциплін і засвоєнні студентами міждисциплінарних знань. Професійні навички журналіста-оператора мають містити не лише технічні аспекти (роботу з камерою, якість зображення, композицію, кут зйомки, освітлення), але й розуміння вимог сучасної журналістики та володіння усіма її жанрами, знання основ психології, ознайомлення зі специфікою кіновиробництва.

In this article you will read about professional aspects of preparation of journalistsoperators. They are based on a complex access to teaching professional disciplines and learning connected with other subjects. Professional education of a journalist-operator has to include not only technical skills (work with camera and other TV machinery, quality of image, composition, angle and place of filming, lightning, knowledge of directing’s and montage’s foundations). Such education has to combine understanding of modern journalistic requisitions, knowledge of all its genres and possibility to use them, familiarization with specificity of film production etc. This type of journalists-operators’ preparation will help to prepare multipurpose workers of mass media who will be able to satisfy informational and aesthetic inquiries of audience and demanded traditional and new media. Beside this, future professionals of traditional and new media have to work out inside of themselves psychological stability and professional erudition. Also they have to be communicative. These skills will help them to avoid stress in their work. Professional journalist-operator has to predict thoughts of people that he is interviewing and fix needed for material phrases and words in time. In work of journalist-operator artistic taste is very important. It is not enough to know only technical characteristic of a camera, laws of light and composition.
Basic elements and features of journalist-operator’s preparation
Keywords: телевізійний оператор; операторська майстерність; візуальні технології; професійна освіта; специфіка роботи; camera operator; cameraman’s skills; visual technologies; professional education; specificity of work; 070; 778.53]– 057.875; 378.091.2